Tensiones en el desarrollo psicomotriz, de los niños y niñas de 1 a 3 años del centro infantil del buen vivir “Gotita de Amor”, del sector Pilacoto, parroquia Guaytacama, del cantón Latacunga - Barrionuevo Hidalgo, Mayra Alexandra (2017)
This project, whose title belongs to "Tensions in the psychomotor development of children from 1 to 3 years at CIBV (Children's Center of Good Living) Gotita de Amor from the rural area Pilacoto, Guaytacama Parish, Latacunga city", it was about the tensions problem that show the indicated population and that directly affect the adequate development of its teaching-learning process, nowadays the needs and demands do not have the institutional capacities in terms of child development and its corresponding sub-levels, this situation responds to families and the community were performed in an individualized way so that each child is recognized as a unique and unrepeatable human being with his own characteristics and learning rhythms. These details require the teacher to maintain a priority respect for each individual differences necessarily adopting their work to each students in terms of rhythm and style of learning., the objective of determining the tensions that affect psychomotor development has been drawn in order to detect the weaknesses of children from 1 to 3 year at Children's Center of good living "Gotita de Amor" from the rural area Pilacoto, Guaytacama,Parish, Latacunga.city The methodology of work was a search, study and bibliographic analysis and printed that allow the elaboration of the scientific-technical foundation through bibliographic fiches; (Observation, interview and survey) in order to do conclusions and general recommendations on the proposed problem that lead to the creation of new methodological strategies for the direct beneficiaries of the same institution), as a final product and Pedagogical innovation that contributes to raise the quality of the teaching-learning process of the children from 1 to 3 years studied.